Emerging Applications of Bedside 3D Printing in Plastic Surgery - Chae, Michael P.; Rozen, Warren M.; McMenamin, Paul G.; Findlay, Michael W.; Spychal, Robert T.; Hunter-Smith, David J. (Frontiers in Surgery, 2015)
Modern imaging techniques are an essential component of preoperative planning in plastic and reconstructive surgery. However, conventional modalities, including three-dimensional (3D) reconstructions, are limited by their representation on 2D workstations. 3D printing has been embraced by early adopters to produce medical imaging-guided 3D printed biomodels that facilitate various aspects of clinical practice. The cost and size of 3D printers have rapidly decreased over the past decade in parallel with the expiration of key 3D printing patents. With increasing accessibility, investigators are now able to convert standard imaging data into Computer Aided Design (CAD) files using various 3D reconstruction softwares and ultimately fabricate 3D models using 3D printing techniques, such as stereolithography (SLA), multijet modeling (MJM), selective laser sintering (SLS), binder jet technique (BJT), and fused deposition modeling (FDM). Significant improvements in clinical imaging and user-friendly 3D software have permitted computer-aided 3D modeling of anatomical structures and implants without out-sourcing in many cases. These developments offer immense potential for the application of 3D printing at the bedside for a variety of clinical applications. However, many clinicians have questioned whether the cost-to-benefit ratio justifies its ongoing use. In this review the existing uses of 3D printing in plastic surgery practice, spanning the spectrum from templates for facial transplantation surgery through to the formation of bespoke craniofacial implants to optimize post-operative aesthetics, are described. Furthermore, we discuss the potential of 3D printing to become an essential office-based tool in plastic surgery to assist in preoperative planning, patient and surgical trainee education, and the development of intraoperative guidance tools and patient-specific prosthetics in everyday surgical practice.